Charring rates for double beams made from laminated veneer lumber (LVL). (6th February 2012) - Tsai, Kevin; Carradine, David; Moss, Peter; Buchanan, Andrew
SUMMARY This paper examines charring rates for different cross‐sections of single and double timber beams made from laminated veneer lumber, with nailed, screwed or glued connection types for the double beams. Charring rates and burning characteristics were examined both in a small furnace and in a larger pilot furnace. The bottom charring rates were sometimes greater than the side charring rates for very narrow beams dominated by corner effects and for double beams where the two components could separate during the fire exposure. The nail‐connected double laminated veneer lumber beams experienced the largest separation, leading to charring between the two components. The best performance was from the glued connection, which showed similar charring rates as a solid timber beam. Both the large‐scale and small‐scale testing showed that suitably placed screws (preferably full‐length threaded) can be used to give almost the same performance as a glued connection. Experimental findings were compared with results from a finite element analysis. There was reasonable agreement while the char layer was small, but less agreement in later stages as the char layer increased in thickness. Experimental findings were used to modify a spreadsheet design tool that predicts the fire resistance of a timber–concrete composite floor. Copyright © 2012 John Wiley & Sons, Ltd.